Determining the effect of one decade on fitness of elite Austrian youth soccer players using propensity score matching - Christoph Gonaus; Christoph Gonaus; Erich Müller; Thomas Stöggl; Thomas Stöggl; Jürgen Birklbauer (Frontiers Media S.A., 2023)
Current trends in attacking strategies and increases in external workload have led to a need for fast and well-conditioned athletes in modern soccer. More recently, progressions in speed, coordination, power and endurance were found over a decade in elite Austrian youth players. However, possible confounders such as relative age, maturation, learning effects, and academy philosophy may have influenced these changes. The present study aimed to determine the decade effect on fitness under statistical control of players' exact age, height, body mass, test location as well as total number of pretests and time interval between test and pretest. Players annually completed a battery of anthropometric, general and soccer-specific fitness tests. MANCOVA was calculated to identify the overall impacts of the covariates on fitness. To balance the covariates of initially 2,530 "former" (2002 to 2005) and 2,611 "recent" (2012 to 2015) players, 1:1 nearest neighbor propensity score (PS) matching was used, resulting in 587 U13, 573 U14, 475 U15, 325 U16, 262 U17, and 129 U18 matched pairs. The decade effect on fitness was assessed by independent t-tests and Cohen's d separately at each age group. Superior performances of recent players were found for linear sprint across all age categories (d = 0.154-0.476) as well as for agility (d = 0.125-0.340) and change-of-direction speed (d = 0.172-0.466) in U15 to U18. Reaction speed increased in U13 (d = 0.288) and U15 (d = 0.310). Flexibility reduced over the decade in all age categories (d = −0.151 to −0.589) and upper-limb power decreased (d = −0.278 to −0.347) in U13 and U14. Balancing the covariate distribution via PS matching generally confirmed previous findings, with fitness decade effects reflecting the athletic needs for modern soccer. Since fitness performance changed over time, reference values should be periodically updated. Coaches favor both physical and cognitive fast players nowadays. Thus, training should target all aspects of speed, without disregarding flexibility, upper-limb power and other preventive strategies that keep the players on the pitch.